The Perils of Entanglement: Bilateral Donors, Faith-Based Organisations and International Development (abstract) - Gerard Clarke (Revue Internationale de Politique de Développement)
The faith and development interface has become a significant feature of development discourse and policy over the last 15 years. While most of the recent literature treats it as a welcome and positive development, leading to productive engagement between donors and faith communities, the new interface has also proven challenging for donors and faith leaders alike. This chapter explores recent initiatives by European bilateral donors to engage with faith-based organisations (FBOs) and efforts by faith communities to create conditions for productive engagement. It also examines some of the resulting controversies and suggests that both donors and FBOs have some distance to travel in creating the conditions and mechanisms that would enable them to work together effectively to combat poverty and social exclusion.